Alternate Conilict Avoidance With Descent in Front of the Intruder - Magister, Tone (Promet - Traffic&Transportation, 2005)
The relative speeds of aircraft in possible conflict encounterare soaring up to or even above 0.5km/s, meaning that the periodof time which includes conflict detection, reaction, andstrategical resolution of conflict, etc., before initiation of conflictavoidance maneuvering is short. Therefore, and since currentground based systems for managing, controlling and handlingaircraft movements is near its maximum capacity, the existingground based control has to be enhanced by the autonomousanti-collision and anti-conflict airborne system. Avoidanceprocedures with descent in front of the intruder are demonstratedas a continuation of autonomous airborne separationresearch begun with conflict avoidance involving descentbehind the intruder. The following continuation is necessQ/ybecause descending behind the intruder is a safe avoidanceonly when initial vertical separation exceeds the defined verticalseparation minimum.